AUTOMATIC WATERING SYSTEM BASED ATMEGA328 MICROCONTROLLER ON GREEN DELI HONEY GUAVA PLANTS - Zul Azhar; Fathurrahman Fathurrahman; Zul Mahadi Nata (Universitas Islam Negeri Sumatera Utara Medan, 2020)
The role of water is very important in the growth process of the green deli honey guava plant, because this plant absolutely requires regular and sufficient water especially during the dry season. One of the obstacles for guava farmers is the problem of watering. Where honey guava has a moisture percentage ranging from 60% to 80% which must be maintained so that the quality of honey guava fruit is better. From these problems, an automatic watering device is designed based on soil moisture. Where this tool can also be monitored via android, LCD, and computer (PC) to make it easier for farmers to monitor. This study aims to determine the effect of soil moisture and assist farmers in controlling soil moisture in the cultivation of deli honey guava. The benefit of this research is to help farmers in an accurate and measurable process of watering plants. This research was conducted in Mancang Village, Binjai City. In this study, 2 honey guava trees were used to be tested using an automatic plant watering tool. One guava tree uses the manual method and the other is controlled using an automatic sprinkler. In this process the data is retrieved via a computer via USB with the PLX-DAQ software. The results showed that the soil moisture of the honey guava tree which was controlled using automatic sprinklers was more stable in maintaining soil moisture of 60% to 80% compared to the honey guava tree which was watered manually because the percentage of soil moisture did not match the plant's needs. Thus, the watering process using this tool is more controlled and measured in maintaining soil moisture in accordance with the needs of the green deli honey guava plant.